The Relationship Between Indicators of Nasal Respiratory Function and Spirometric Parameters in Children With Bronchial Asthma - Krasilnikova, Svetlana V.; Khramov, Alexey A.; Khramova, Regina N.; Ovsyannikov, Dmitry Yu.; Daniel-Abu, Mojisola I.; Novozhilov, Alexey; Shahov, Andrey V.; Kubysheva, Nailya I.; Eliseeva, Tatyana I. (Frontiers in Pediatrics, 2021)
Introduction. The relationship between objective indicators of nasal obstruction and airflow limitation in children with bronchial asthma (BA) and allergic rhinitis (AR) has not yet been studied. Objective: To study the relationship between objective parameters of nasal obstruction and airflow limitation, determined using the methods of anterior active rhinomanometry (AARM) and spirometry in children with BA and AR. Materials and methods. 88 children and adolescents with BA and AR, boys - 65.9 % (58/88), were examined. The median age was 11.09 [10.42; 11.76] years. To determine airflow limitation, the following spirometric parameters were evaluated: the forced vital capacity of the lungs (FVC), the forced expiratory volume in 1 second (FEV1), the ratio of FEV1/FVC, and maximum expiratory flow at the point 25% of the flow-volume loop (MEF25). Data were recorded both in absolute values and in relative units (% pred). Nasal respiratory function was determined by anterior active rhinomanometry based on the total nasal airflow (TNAF) in absolute (Pa/cm3/s) and relative units (RTNAF, % pred). Results. In the general cohort and in boys but not in girls, a statistically significant direct correlation was found between TNAF (Pa/cm3/s) and absolute spirometry parameters of bronchial patency – all had p <0.01. Also, RTNAF and relative MEF25 values (% pred) in the general cohort were R=0.22, p=0.04, and in boys, R=0.28, p=0.03. In girls, there was no statistically significant correlation between nasal respiratory function and spirometric parameters, all p>0.05. Additional analysis of literature was conducted to ascertain that the identified gender differences were not occasional. Conclusion. The significant positive correlation of absolute values of AARM and spirometric parameters in children with BA and AR was established, which apparently reflects the physical development of children. Of all the relative indicators of spirometry, only MEF25 (% pred), which indirectly reflects the patency of small bronchi, had a distinct direct correlation with RTNAF. These patterns are clearly expressed in boys with BA. In girls with this disease, however, the relationship between nasal respiratory function and spirometric indicators seems to be more complex and requires further study.